Lower Expression of miR-26a in PBMCs Indicates the Occurrence of Early-Onset Neonatal Sepsis and Is Partly Mediated by the Upregulation of PTEN - Ziyan Zhao (Frontiers in Pediatrics, 2021)
Aim: It is difficult to identify neonatal sepsis early due to the lack of specific markers. The aim of the present study was to explore whether miR-26a expression in peripheral blood mononuclear cells (PBMCs) could be used as a diagnostic marker of the disease and whether phosphatase and tensin homolog (PTEN) was involved in suppressing miR-26a expression.Methods: A total of 51 early-onset septic newborns and 102 healthy newborns were included. Blood specimens were collected from septic newborns at the time of clinical diagnosis (baseline) and again between 72 and 96 h after birth. Blood specimens were collected from healthy newborns on admission. The expressions of miR-26a and PTEN in PBMCs were measured using real-time quantitative PCR (RT-qPCR). Other data, including hemoculture, were collected from medical records.Results: In septic newborns with and without a positive hemoculture, a lower baseline level of miR-26a in PBMCs was associated with a higher risk of disease. Additionally, at baseline, there was a certain linear relationship between the levels of miR-26a and two serological inflammatory markers (i.e., white blood cell count and C-reactive protein level) in septic newborns. In addition, the baseline expressions of miR-26a and PTEN showed a reverse linear relationship. Compared with those at baseline, the expression of miR-26a was higher and the expression of PTEN was lower in septic newborns starting at 72 h after birth.Conclusion: A lower baseline miR-26a expression in PBMCs indicated the occurrence of early-onset neonatal sepsis, and a reduced miR-26a expression might be partly related to the inflammatory process and PTEN upregulation.